The Effect of Health Education about Labor Pain Management on the Knowledge Level of Pregnant Women at Sewon II Health Center, Bantul Yogyakarta - Arika Nur Fadzillah; Dwi Susanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Labor is the expulsion of the conception product which is marked by the release of the fetus, placenta, and amniotic membranes. Labor pain is a condition whereby almost all pregnant women experience physiological discomfort, especially in the last trimester. Therefore, reducing labor pain can be done by, one of the ways, increasing the knowledge of pregnant women about non-pharmacological labor pain management. The study aimed at determining whether there is any effect of health education about labor pain management on the level of knowledge of pregnant women at Puskesmas (Community Health Center) Sewon II Bantul, Yogyakarta. The design of the study was the Quasy-Experimental Design method with the pretest and posttest one-group design. The sampling technique used was purposive sampling with a total sample of 37 respondents. Data were analyzed using the Wilcoxon Signed Rank Test. The results of the study showed that the knowledge level of pregnant women before being given health education about non-pharmacological labor pain management was in the sufficient category with 20 respondents (54.1%) and the knowledge level of pregnant women after being given health education about non-pharmacological labor pain management was in the good category with 36 respondents (97.3%). There is an effect on the difference in the knowledge level of pregnant women before and after being given health education about non-pharmacological labor pain management.